Stainless green: Considerations for making green steel using carbon capture and storage (CCS) and hydrogen (H2) solutions - Hasan Muslemani (The Oxford Institute for Energy Studies, 2023)
Steelmaking is one of the two largest industrial contributors to climate change, accounting for 7-9% of global CO2 emissions. To achieve drastic emission reduction in the steel sector, integrating breakthrough low-carbon technologies such as carbon capture and storage (CCS) technology and hydrogen (H2) solutions become necessary. However, the applicability of both solutions and their potential for lowering emissions hinges on several technical, economic and political factors. This paper sheds light on these factors and discusses the green steel 'premium' and which industries are likely to become early adopters of green steel products. This work also highlights the different forms of competition that greener steels would be subject to in the market, including implications on global trade, and how governments and the private sector can help mobilize investment into these solutions.
Keywords: 330; Carbon Capture and Storage; carbon management; CCS; Climate Policy; Energy Transition; Green steel; Hydrogen; Industrial Decarbonization; steel making